Draft Genome Sequence of CO33, a Coffee-Infecting Isolate of Xylella fastidiosa - Giampetruzzi, Annalisa (Genome Announc, 2015)
The draft genome sequence of Xylella fastidiosa CO33 isolate, retrieved from symptomatic leaves of coffee plant intercepted in northern Italy, is reported. The CO33 genome size is 2,681,926 bp with a GC content of 51.7%.